HUBUNGAN DAYA TERIMA MAKANAN DENGAN KUALITAS DIET PADA SANTRI - Nida Nur Amalia; Fillah Fithra Dieny; Aryu Candra; Choirun Nissa (GIZI INDONESIA, 2023)
Santri is one of the adolescent age groups who are prone to problems with food intake and low quality of diet and become one of the factors causing nutritional problems in the next phase of life. Nutrition compliance for a student depends on food service management, and an indicator of a student’s food quality is needed. The purpose of this study was to analyze the correlations between food acceptance and diet quality in Islamic boarding school students. This study was observational with a cross-sectional design. This study was held in Askhabul Kahfi Islamic Boarding School Semarang and consisted of 69 subjects chosen by simple random sampling. Diet quality data was measured through the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and Diet Quality Index - International (DQI-I), food acceptance data were collected using questionnaires and food waste forms. The data were analyzed by the Pearson correlation test. This study showed that 66 subjects (95,7%) had a low diet quality and only 4,3 percent of subjects have high nutrition knowledge. There was no correlation between food acceptance and diet quality (p=0.346), but the components of diet quality which is variation score indicated significant positive correlations with a variety of food menus (p=0.020) and significant negative correlations between food acceptance with overall balance score (p=0.030). There was no correlation between food acceptance with diet quality among Santri. The incompatibility of portion standards with dietary recommendations was the most influential factor in food acceptance and diet quality of santri.Keywords: food acceptance, diet quality, santri, nutrition knowledge ABSTRAK Santri merupakan kelompok usia remaja yang rentan mengalami masalah asupan makanan maupun rendahnya kualitas diet dan menjadi salah satu faktor penyebab masalah gizi pada fase kehidupan selanjutnya. Pemenuhan gizi pada santri sangat bergantung pada penyelenggaraan makanannya, sehingga diperlukan indikator mutu kualitas makanan yang diberikan. Tujuan penelitian ini untuk menganalisis hubungan antara daya terima makanan dengan kualitas diet pada santri. Penelitian observasional dengan desain cross sectional. Penelitian dilaksanakan di Pondok Pesantren Askhabul Kahfi Semarang dengan 69 subjek dipilih menggunakan metode simple random sampling. Data kualitas diet diukur menggunakan Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) dan formulir Diet Quality Index – International (DQI-I), daya terima makanan dengan formulir sisa makanan dan kuesioner. Data dianalisis dengan uji korelasi Pearson. Hasil analisis menunjukkan 95,7% subjek memiliki kualitas diet rendah dan hanya 4,3 persen subjek yang memiliki pengetahuan gizi tinggi. Tidak ada hubungan signifikan antara daya terima makanan dengan kualitas diet (p=0,346) namun komponen kualitas diet yaitu skor variasi memiliki hubungan positif signifikan dengan variasi menu (p=0,020), dan skor keseimbangan keseluruhan memiliki hubungan negatif signifikan dengan daya terima makanan (p=0,030). Tidak ada hubungan antara daya terima makanan dengan kualitas diet pada santri. Ketidaksesuaian standar porsi dengan rekomendasi kebutuhan.Kata kunci: daya terima makanan, kualitas diet, santri, pengetahuan gizi